(untitled) (Itinera, 2015)
This essay aims at clarifying the relation between the notions of formativity and improvisation, with particular attention to musical practices. Firstly, I will focus on originality and exemplarity, then I will briefly deepen three themes of particular interest faced by Pareyson’s philosophy of art: 1) the unforeseen; 2) the interpretation; 3) the cue or sketch. My purpose is to suggest some adjustments to the notion of formativity, in order to outline the essential features of a logic of musical improvisation.